Application of Cox Regression Model to Analyzing the Duration of Academic Continuation for University Enrollment Data in the Mathematics Department at the Faculty of Education in Ubari from 2008 to 2021 (Sebha University Conference Proceedings, 2025)
This research paper aims to develop a deep understanding of the extent of student retention in the Mathematics Department at the Faculty of Education in Ubari by applying the Cox regression model to university enrollment data from Spring 2008 to Fall 2021. The practical objective is to review and solidify the foundations and concepts related to the analysis of academic retention duration through a case study in the education sector. The study includes analyzing the duration of stay of 315 students over 26 consecutive semesters, from their enrollment as "enrolled" until their departure from the institution (graduated or dropped out).In this paper, a Cox regression model was formulated and estimated using the R programming language, considering the student's status (staying/leaving) and duration of stay as dependent variables, and gender, nationality, and cumulative GPA as explanatory variables.The results of the model estimation and diagnostics showed that the gender and nationality factors do not have statistically significant effects on the student's duration of stay. In contrast, the cumulative GPA estimates showed a statistically significant effect on the students' academic persistence at the university, with students having higher GPAs tending to stay for shorter periods, and vice versa. These results highlight the importance of academic performance in determining students' trajectories and provide valuable insights that can be utilized in developing student support strategies and enhancing their academic persistence.